Bilbliometric Analysis of Euthanasia in the Perspective of Medical Ethics - Yuniarti, Elsa; Jessi Rizkanauli Simangunsong; Aditiya Ramadhani; Nabila Azzahra (Frontiers on Healthcare Research, 2025)
Background: Euthanasia has emerged as a critical topic of debate in society, encompassing both public discourse and private considerations within medical, legal, and ethical domains. The concept, which involves death with or without physician assistance, has gained significant attention due to its complex implications for human rights, medical ethics, and professional practice. The development of euthanasia policies in various countries has raised new challenges related to conscientious objection and medical practice adjustments. Methods: This study employed a bibliometric analysis approach using Scopus as the primary data source. The search query focused on "euthanasia in medical ethics perspective" for publications from 2016 to 2024. Data cleaning and transformation were conducted using OpenRefine, while VOSviewer software (version 1.6.6) was utilized for data analysis and visualization, generating network, overlay, and density visualizations to identify publication trends across various metrics. Results: The analysis revealed significant fluctuations in euthanasia-related publications from 1976 to 2024, with notable peaks in 1992, 1996, and 2000. The United States emerged as the leading country in publications, followed by significant contributions from the Netherlands and Belgium. Medical disciplines dominated the subject areas (45.2%), followed by nursing (9.7%) and social sciences (5.9%). The research identified three main clusters in global euthanasia research: one focusing on humanitarian and ethical aspects led by the United States, another centered on legalization progress led by Belgium and the Netherlands, and a third cluster examining death and legal aspects. Conclusion: Euthanasia research shows diverse disciplinary contributions, with medical perspectives dominating but requiring integration with nursing and psychological insights for comprehensive policy development that respects patient values.